Toward quasi-solid state Dye-sensitized Solar Cells: Effect of γ-Al2O3 nanoparticle dispersion into liquid electrolyte. (January 2015) - Sacco, Adriano; Lamberti, Andrea; Gerosa, Matteo; Bisio, Chiara; Gatti, Giorgio; Carniato, Fabio; Shahzad, Nadia; Chiodoni, Angelica; Tresso, Elena; Marchese, Leonardo
Graphical abstract: Highlights: γ-Al2 O3 nanoparticles were prepared with a fast chemical synthesis route. γ-Al2 O3 NPs were dispersed in a commercial electrolyte to increase its viscosity. Optical measurements demonstrate a light scattering effect due to NP inclusion. The NP-based electrolyte exhibits faster charge diffusion. The presence of NPs improved the long-term stability of the DSCs. Abstract: In this study, we report on the effect of γ-Al2 O3 nanoparticle (NP) addition into liquid electrolyte for Dye-sensitized Solar Cell (DSC) application. γ-Al2 O3 was prepared by a fast ultrasound-assisted sol–gel procedure allowing the formation of γ-Al2 O3 crystals with nanometric size and high specific surface area. A quasi-solid state electrolyte was prepared by dispersing 5 wt% of γ-Al2 O3 NPs in commercially available electrolytic solution, and optical and electrical properties were analyzed and compared to the bare liquid electrolyte. DSCs were fabricated exploiting NP-based electrolyte and fully characterized. In comparison with liquid electrolyte-based cells, the quasi-solid ones exhibit the same photovoltaic performances and a noticeable extended stability over the time.